Combined Application of Antibrowning, Heat Treatment and Modified‐Atmosphere Packaging to Extend the Shelf Life of Fresh‐Cut Lotus Root. Issue 6 (28th April 2015) - Son, Jihye; Hyun, Jeong‐Eun; Lee, Jo‐Won; Lee, Sun‐Young; Moon, BoKyung
Abstract This work aimed to determine the effects of different concentrations of antibrowning treatments (that is, distilled water [DW], 1% ascorbic acid [AA], 0.5% chamomile [CM], and 1% AA + 0.5% CM) and heat‐treatment (55 °C for 45 s) combined with packaging under 4 different modified‐atmosphere gas compositions (that is, air, vacuum, 100% CO2, 50% CO2/50% N2) on the quality and microbiological characteristics of fresh‐cut lotus root. The quality characteristics (that is, color, weight loss, texture, pH, polyphenoloxidase activity, and total phenolic content) of the AA + CM‐dipped sample in 100% CO2 packaging were maintained significantly better than those of the other samples (P < 0.05). The microbiological counts observed in the DW‐dipped sample during storage were higher than those of the AA, CM, and AA + CM samples, and heat‐treatment retarded the microbiological deterioration of fresh‐cut lotus root. Therefore, the results revealed that dipping in an antibrowning treatment (AA + CM), and 100% CO2 MAP with heat treatment effectively extend the shelf life of fresh‐cut lotus root to 21 d at 5 °C.